2021
DOI: 10.1021/acsami.1c06350
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Ruddlesden-Popper Faults in Cesium Lead Bromide Perovskite Nanocrystals for Enhanced Optoelectronic Performance

Abstract: While the layered hybrid Ruddlesden-Popper (RP) halide perovskites have already established themselves as the frontrunners among the candidates in optoelectronics, their all-inorganic counterparts remain least explored in the RP-type perovskite family. Herein, we study and compare the optoelectronic properties of all-inorganic CsPbBr3 perovskite nanocrystals (PNCs) with and without RP planar faults. We find that the RP-CsPbBr3 PNCs possess both higher exciton binding energy and longer exciton lifetimes. The fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…However, the formation mechanism of the RP planar faults remained unknown. [ 25 ] As can be seen from the above studies, the RP planar faults in the prepared perovskite materials by the solution method were identified, and the corresponding physical mechanisms of the RP planar faults were obtained, but a more systematic in‐depth analysis of the structure‐property relationship was still lacking.…”
Section: Resultsmentioning
confidence: 99%
“…However, the formation mechanism of the RP planar faults remained unknown. [ 25 ] As can be seen from the above studies, the RP planar faults in the prepared perovskite materials by the solution method were identified, and the corresponding physical mechanisms of the RP planar faults were obtained, but a more systematic in‐depth analysis of the structure‐property relationship was still lacking.…”
Section: Resultsmentioning
confidence: 99%
“…Although defects in ILHPs typically are not desired for solar cell applications, some defects can improve ILHPs’ properties, making ILHPs attractive for other applications. For example, the Ruddlesden–Popper faults, a type of planar defect, can increase the excitation binding energy and prolong the excitation lifetimes of CsPbBr 3 nanocrystals, making the nanocrystals suitable for LEDs. It would be ideal that defects can be manipulated for a specific purpose. Therefore, further investigation of defects in self-assembled micro-/nanostructures of ILHPs should facilitate these applications.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that mixed 2D/3D perovskites can show high electrical and photo efficiency for both, high-property photovoltaic [80][81][82][83][84][85][86][87] and LEDs. 9,15,71,74,[88][89][90] Using BA as a spacer to form RP perovskite BA 2 Cs nÀ1 Pb n (Br/X) 3n+1 (X = Cl, I) from inorganic CsPb(Br/X) 3 (X = I or Cl), the number of planes of CsPbBr 3 in the structure is around B24 AE 7. 15 These large n-value materials show that quasi-2D/3D structures can balance the thin emission line width and high QY of thin nanosheets with the superior conduction properties of thicker perovskite crystals.…”
Section: D/3d Heterostructure Rp Perovskitementioning
confidence: 99%
“…9 The RP-CsPbBr 3 perovskite nanocrystals possess higher exciton binding energy and longer exciton lifetimes than all inorganic CsPbBr 3 perovskite. 74 MA x DMAPbBr 3+x perovskite was prepared by mixing dimethylammonium (DMA) and MA cations. The 2D/3D mixed perovskite trimethylsilyl methylamine (TmMA)-modified MA x DMAPbBr 3+x was formed by adding branched cation (TmMA + ).…”
Section: D/3d Heterostructure Rp Perovskitementioning
confidence: 99%
See 1 more Smart Citation